Pengaruh Model Pembelajaran Active Knowledge Sharing Terhadap Hasil Belajar IPA SMP Negeri 1 Moro’o Tahun Pelajaran 2024/2025 - Gesiterang Waruwu; Listen Arahan Zega; Fita Kristiani Ndraha (GEN BIONIX: Jurnal Ilmiah Pendidikan Biologi, 2025)
The low learning outcomes of Natural Sciences (IPA) at SMP Negeri 1 Moro'o are caused by the learning process which is still teacher-centered and the lack of variety of learning models that actively involve students. This study aims to analyze the effect of the Active Knowledge Sharing learning model on the learning outcomes of eighth grade students in the human digestive system. An experimental method with a randomized control-group pretest-posttest design was used in this study, involving two randomly selected classes, namely the experimental class that applies the Active Knowledge Sharing model and the control class that uses conventional learning. The research instrument was a five-item essay test that had gone through logical validation and trials to ensure validity, reliability, difficulty level, and discriminatory power. Data were analyzed using normality tests, homogeneity tests, and hypothesis tests with two-tailed t-tests at a significance level of 5%. The results showed that the average learning outcomes of the experimental class reached 81.50 with a good category, while the control class only reached 73.57 with a sufficient category. The hypothesis test yielded a t-value of 3.967, which was greater than the t-table of 1.677, thus the alternative hypothesis was accepted. This finding demonstrates a significant effect of the Active Knowledge Sharing learning model on improving students' science learning outcomes. This learning model is effective in encouraging active student participation through knowledge sharing and teamwork, making it an alternative student-centered learning strategy.